Family-level diversity of Coleoptera (Insecta) from the Nanling Mountains and the Greater Bay Area, China - Liu, Zhenhua; Li, Zhiqiang (Zootaxa, 2024)
Coleoptera comprise 198 families and over 440,000 species to date, of which 143 families and over 35,000 species are known in China. Of these, only 64 families have been recorded in Guangdong Province, fewer than in Hong Kong. To investigate the insect diversity of Guangdong, numerous specimens were collected from the Nanling Mountains and the Greater Bay Area using various methods, and over 200,000 specimens of Coleoptera were assigned to families. Thus, a preliminary study of beetles at the family-level in Guangdong is carried out based on the examined specimens and historical records. An updated checklist of beetle families in Guangdong increases the number of families from 64 to 111, in which Eupsilobiidae is recorded for the first time in China and a new species, Eidoreus haizhuensis sp. nov. is described here, demonstrating the importance of persistent collecting with different methods for the study of insect diversity. Habitus images of most of the beetle families occurring in Guangdong are provided. And the updated records are compared in detail with the published records, showing that more families may potentially be found in Guangdong, requiring further field work and taxonomists working on niche groups.